1998
DOI: 10.1351/pac199870040903
|View full text |Cite
|
Sign up to set email alerts
|

Radical copper oxidases, one electron at a time

Abstract: Radical copper oxidases (including the fungal enzymes galactose oxidase and glyoxal oxidase) are emerging as an important family of metalloenzymes based on the free radical-coupled copper catalytic motif. The active sites of these enzymes combine a redox active copper ion with a stable protein free radical, forming a two-electron redox unit capable of oxidizing a variety of alcohols and aldehydes with reduction of dioxygen to hydrogen peroxide. This active site is remarkable in the extent to which the ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 10 publications
1
57
0
Order By: Relevance
“…This displacement is coupled to a protonation event that implies that Tyr 495 can serve as a general base, capable of activating bound substrate by proton abstraction. A tryptophan residue (Trp 290 ) stacked over the thioether side chain (13) is thought to contribute to the unusual stability of the free radical-containing form of this enzyme, which can persist for weeks in the absence of reductants (20,21). Spectroscopic studies on the glyoxal oxidase (5) provide evidence for an active site structure nearly identical to that found in galactose oxidase, despite the distinct catalytic function.…”
Section: Glyoxal Oxidase (Glox)mentioning
confidence: 99%
“…This displacement is coupled to a protonation event that implies that Tyr 495 can serve as a general base, capable of activating bound substrate by proton abstraction. A tryptophan residue (Trp 290 ) stacked over the thioether side chain (13) is thought to contribute to the unusual stability of the free radical-containing form of this enzyme, which can persist for weeks in the absence of reductants (20,21). Spectroscopic studies on the glyoxal oxidase (5) provide evidence for an active site structure nearly identical to that found in galactose oxidase, despite the distinct catalytic function.…”
Section: Glyoxal Oxidase (Glox)mentioning
confidence: 99%
“…Concurrently with the above work we prepared L 6 , which is a bidentate ligand containing an (Fig. 3) [31].…”
Section: Modeling the Tyrtrp π-π Interactionmentioning
confidence: 95%
“…Deconvolution of the voltammograms showed that the half-lives of 6 2+ and 7 2+ at 295 K were identical to each other within experimental error. Hence, the π-π interaction in 6.BF 4 has no bearing on the stability of the [L 6• ] + radical, beyond affording it some steric protection.…”
Section: Modeling the Tyrtrp π-π Interactionmentioning
confidence: 99%
See 2 more Smart Citations